PEMBELAJARAN MATEMATIKA MODEL IDEAL PROBLEM SOLVING DENGAN TEORI PEMROSESAN INFORMASI UNTUK PEMBENTUKAN PENDIDIKAN KARAKTER DAN PEMECAHAN MASALAH MATERI DIMENSI TIGA KELAS X SMA - Nayazik, Akhmad; Sukestiyarno, Sukestiyarno (PYTHAGORAS Jurnal Matematika dan Pendidikan Matematika, 2012)
This study aims to: (1) generate a valid learning tool and (2) the implementation of an effective learning device. Development of learning tools using a modified model of Thiagarajan. Techniques of data analysis with descriptive analysis, test mastery learning using t-test, z proportions, regression testing, and test for normality gain. The results showed that: (1) a device developed has been declared valid by the validator with an average score of 4.18 for the syllabus, 4.24 for RPP, 4.35 for LKS, 4.37 for the Student Book, 4,00 for the TKPM and (2) test devices produce (a) mastery of problem-solving ability of students eligible 75,00 statistically complete with average 77.58 (b) curiosity and problem solving skills positively by 63.7% of the problem-solving abilities with equation Y = -11.120 + 0.988X1 + 0.941X2 (c) increase the curiosity of 4 selected samples ranged from 0.33 to 0.58 and problem solving skills ranged from 0.31 to 0.41 are included in the medium category (d) affect the learning process of the formation of character education and problem solving include attention, memory, thinking processes, and response.Keywords: IDEAL Problem Solving, Information Processing Theory, Character Education